Validation of the Preschool Attachment Rating Scales with child-mother and child-father dyads. Issue 5 (2nd September 2020) - Deneault, Audrey-Ann; Bureau, Jean-François; Yurkowski, Kim; Moss, Ellen
ABSTRACT: Growing evidence points to the theoretical and statistical advantages of continuous (rather than categorical) assessments of child-caregiver attachment. The Preschool Attachment Rating Scales (PARS) is a continuous coding system to assess preschool attachment that is complementary to the categorical MacArthur Preschool Attachment Coding System (PACS). The current study aims to evaluate the reliability and validity of the PARS to measure both child-mother and child-father attachment during the preschool period. Participants included 144 preschool-aged children ( M = 46.89 months, SD = 8.77; 83 girls) and their parents. Results support the reliability and validity of the PARS: good inter-rater reliability, expected associations between scales, convergence with the PACS, and association with parental sensitivity and child externalizing problems. These findings support the application of continuous assessments of child-caregiver attachment in the preschool years. They also align with previous work on child-mother attachment, and present avenues for future research on child-father attachment.